1992
DOI: 10.1002/hyp.3360060202
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the effects of spatial variability of infiltration on the output of a distributed runoff and soil erosion model using Monte Carlo methods

Abstract: Monte Carlo procedures were used to evaluate the effects of spatial variations in the values of the infiltration parameter on the results of the ANSWERS distributed runoff and erosion model. Simulation results obtained were compared with measured values. Field infiltration measurements indicated spatial correlation at much smaller distances than the size of an element. Therefore, at first only the error of the mean had to be taken into consideration for block infiltration rates. Consequently, not only single h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Lenhart et al (2002) applied two different approaches to sensitivity analysis on the same model (SWAT). Sensitivity analysis was conducted for the hydrological and soil erosion model LISEM (the Limburg soil erosion model) by De Roo et al (1992). Mendicino (1999) used sensitivity analysis on different GISbased methodologies to estimate the Length-Slope factor in order to determine which of these is more reliable for spatial erosion risk assessment.…”
mentioning
confidence: 99%
“…Lenhart et al (2002) applied two different approaches to sensitivity analysis on the same model (SWAT). Sensitivity analysis was conducted for the hydrological and soil erosion model LISEM (the Limburg soil erosion model) by De Roo et al (1992). Mendicino (1999) used sensitivity analysis on different GISbased methodologies to estimate the Length-Slope factor in order to determine which of these is more reliable for spatial erosion risk assessment.…”
mentioning
confidence: 99%
“…De Roo et al (1992), on the other hand, have examined the eect of varying the spatial pattern in one parameter used in the ANSWERS model. They observed that ANSWERS is very sensitive to in®ltration rates, and that in their study area in®ltration had very low levels of spatial autocorrelation (nugget variance).…”
Section: Applicationmentioning
confidence: 99%
“…Thus, Rewerts and Engel (1991) showed that it was sensitive to the algorithm for calculating slope from a DEM, while Wu et al (1993) showed that ANSWERS provides a more consistent prediction of conditions than AgNPS or CREAMS. Brown et al (1993) have examined the eect of spatial resolution of the database, and De Roo et al (1989Roo et al ( , 1992 have shown that the model is extremely sensitive to in®ltration, both in terms of its absolute amount and its spatial pattern.…”
Section: Spatial Sensitivity Analysis Of Answers the Modelmentioning
confidence: 99%
“…Poiani and Bedford (1995) recently presented a cursory review of GE-based NPS pollution models emphasizing surface applications. Numerous hydrologic-water quality models of runoff and soil erosion have been used with a GIS to determine surface sources of NPS pollutants from watersheds (Pelletier, 1985;Potter et al, 1986;Oslin et al, 1988;Sivertun et al, 1988;DeRoo et al, 1989DeRoo et al, , 1992Rudra et al, 1991;Bhaskar et al, 1992;Drayton et al, 1992;Joao & Walsh, 1992;Tim et al, 1992;Walker et al, 1992;Wolfe, 1992;He et al, 1993;Heidtke & Auer, 1993;Levine et al, 1993;Mitchell et al, 1993;Warwick & Haness, 1994) agricultural areas (Hopkins & Clausen, 1985;Gilliland & Baxter-Potter, 1987;Hession & Shanholtz, 1988Panuska & Moore, 1991;Hamlett et al, 1992;Lee & White, 1992;Geleta et al, 1994;Tim & Jolly, 1994) and urban areas (Smith & Brilly, 1992;Smith, 1993;Ventura & Kim, 1993). In addition, several groundwater models have been coupled to a GIS to simulate water flow and/or NPS pol-lutants in aquifers (Kernodle & Philip, 1989;Baker & Panciera, 1990;Hinaman, 1993;Roaza et al, 1993;El-Kadi et al, 1994;Darling & Hubbard, 1994).…”
Section: Gis-based Models For Nps Pollution Estimationmentioning
confidence: 99%